ANALISIS INTEGRASI SPASIAL PASAR CABAI MERAH KERITING DI JAWA TENGAH DENGAN METODE VECTOR ERROR CORRECTION MODEL - Samantha, Kenia; Tarno, Tarno; Rahmawati, Rita (Jurnal Gaussian, 2021)
Curly red chili (Capsicum annuum L.) is one of commodity which has a big influence to the national economy. To maintain the price stability of curly red chili, an integrated market is needed. Spatial market integration is the level of closeness of relations between regional markets and other regional markets. Spatial market integration will be modeled by the Vector Error Correction Model (VECM) method to see the closeness of both short and long term relationships. The object of this study is the price of curly red chili for several regions in Central Java, such as Kota Semarang, Kab. Demak, Kab. Pati, and Kab. Pekalongan in the period January 2016 to December 2019 where the data has met the stationarity test at first level of difference. In Johansen's cointegration test, it was obtained 3 cointegrations, which means that in each short-term period all variables tend to adjust to each other to achieve long-term balance. Granger causality test shows that there is a two-way relationship and the relationship affects one variable to another for all variables. The VECM model obtained has the MAPE accuracy value for HCMK Semarang 15.93%, Kab. Demak 17.61%, Kab. Pati 15.88%, and Kab. Pekalongan 14.49% which can be interpreted that the performance of the model is good.Â Keywords: Curly Red Chili, Spatial Market Integration, VECM, Johansen's Cointegration, Granger Causality